MASUK DAN BERKEMBANGNYA ISLAM DI KERAJAAN KUTAI KARTANEGARA - Samsir Samsir (Pascasarjana IAIN Metro, 2019)
The condition of Islam in the beginning of its entry in Kutai Kertanegara was still simple. After following developments today as developments in the field of science and technology, the process of spreading Islam has progressed. After Islam was accepted by the king and the people of Kutai in a peaceful manner. So the King of the Crown Prince or the Noble King of Islam ordered his people to abandon the teachings of their religion by replacing Islam. The development of Islamic religious teachings increased rapidly with the birth of several Islamic organizations which not only fought for the interests of a group of people but also maintained the existence of Islam, besides the strategic location of Kutai Kartanegara. The Central Kalimantan region is central, causing it to get migration from all parties which gives rise to races and acculturation of cultures which gives rise to a culture that has a variety of styles. In the 16th century, the migration of the Malay to the East was due to the pressure of political pressure which violently flared in western Indonesia with the fall of Malacca in 1511 AD. The great flow of Malay migration to the East began with capital to Makassar where they controlled spices. -rempah Maluku together with Javanese people. Aceh's expansion of Johor and other regions of the Malacca Peninsula at the beginning of the 17th century. The disruption of the Dutch over Malacca in 1941 AD in Western Indonesia added to the swift flow to the East. With the acceptance of Islam as the official religion of the kingdom by the king of the Crown, all of his people also abandoned the religion previously believed. As a broadcaster on Islam, Lord Tunggang Parangan began teaching about monotheism and the teachings of Islam as a whole. For his patience and tenacity to teach about Islamic teachings, religious teachers and scholars were born who could help continue the mission in developing Islam in Kutai, especially in East Kalimantan. Thus Islam in East Kalimantan can develop both through education, marriage, trade, as well as art and culture.